2018
DOI: 10.1038/s42005-018-0074-8
|View full text |Cite
|
Sign up to set email alerts
|

Tunable electronic structure and topological properties of LnPn (Ln=Ce, Pr, Sm, Gd, Yb; Pn=Sb, Bi)

Abstract: Recently, the rare-earth monopnictide compounds LnPn have attracted considerable attention in condensed matter physics studies due to their possible topological properties. We have performed systematic first principles study of the electronic structure and band topology properties of LnPn (Ln=Ce, Pr, Sm, Gd, Yb; Pn=Sb, Bi). Assuming the f-electrons are well localized in these materials, both hybrid functional and modified Becke-Johnson calculations yield electronic structure in good agreement with experimental… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Meanwhile in SmSb, the analysis of the Shubnikov-de Haas (SdH) oscillations indicates a topologically non-trivial band structure [29]. Topological electronic structures were detected using angle-resolved photoemission spectroscopy (ARPES) for several rareearth mono-bismuthides (Ce, Pr, Sm, Gd)Bi, showing tunable bulk band inversions and corresponding surface states [30], where the ARPES results agree well with density functional theory (DFT) calculations assuming the 4f -electrons to be well localized [32].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Meanwhile in SmSb, the analysis of the Shubnikov-de Haas (SdH) oscillations indicates a topologically non-trivial band structure [29]. Topological electronic structures were detected using angle-resolved photoemission spectroscopy (ARPES) for several rareearth mono-bismuthides (Ce, Pr, Sm, Gd)Bi, showing tunable bulk band inversions and corresponding surface states [30], where the ARPES results agree well with density functional theory (DFT) calculations assuming the 4f -electrons to be well localized [32].…”
Section: Introductionmentioning
confidence: 57%
“…Searching for correlated and magnetic materials with topologically non-trivial electronic structures has recently led to the discovery of novel topological phases, such as topological Kondo insulators [1,2], magnetic topological insulators [3][4][5][6], magnetic Weyl semimetals [7][8][9][10] and Weyl-Kondo semimetals [11,12]. The LnX series crystallizing in the cubic NaCl-type structure [13](Ln = rare-earth and X = As, Sb or Bi) is a large family of semimetals where topologically nontrivial band structures have been found to exist with electronic correlations and magnetism [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. For example, evidence was found that CeSb hosts Weyl fermions in the fieldinduced ferromagnetic state [14], while NdSb was reported to be a Dirac semimetal with antiferromagnetic (AFM) order [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the amplitude of the α-band oscillations is maximum at around 0.8 K, and upon further decreasing the temperature, the amplitude decreases. Meanwhile, the angular dependence of F α can be fitted with the equation for anisotropic three-dimensional ellipsoidal pockets [51](see Supplementary Figure 2), which can describe the anisotropic bullet-like Fermi surface pockets around the X-points, corresponding to the bulk Fermi surface of the α-band [23,29]. However, although the SdH and dHvA data coincide well at higher temperatures, below around 2.5 K there is a significant deviation which cannot be accounted for by the LK formula.…”
Section: Resultsmentioning
confidence: 99%
“…Localized f-electron magnetism in Mott-Hubbard systems has traditionally been a challenge for ab initio Density Func- tional Theory [75,76] (DFT) owing to systematic selfinteraction and static-correlation errors [77] in semi-local approximate exchange correlation (XC) functionals. When fshell magnetism is not important, DFT simulations of rareearth compounds often relegate the f-electrons to a coreshell [78] within a pseudopotential approximation. Such a description yields satisfactory structural property predictions especially in the Lathanides where the f-shell-ligand hybridization is weak [78].…”
Section: Density Functional Theory Simulationmentioning
confidence: 99%
“…When fshell magnetism is not important, DFT simulations of rareearth compounds often relegate the f-electrons to a coreshell [78] within a pseudopotential approximation. Such a description yields satisfactory structural property predictions especially in the Lathanides where the f-shell-ligand hybridization is weak [78]. In KYbSe 2 , magnetism is of primary relevance and so f-electrons need to be treated explicitly as valence electrons.…”
Section: Density Functional Theory Simulationmentioning
confidence: 99%